MINDFUL LANGUAGE TEACHING: ENHANCING LEARNING THROUGH SOCIAL-EMOTIONAL SKILLS - Vulcan Demirkan-Martin (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Social-Emotional Learning (SEL) refers to the process of acquiring and applying the knowledge and skills needed to set and achieve positive goals, understand and manage emotions, feel and demonstrate empathy for others, and build and maintain positive relationships. I regularly integrate SEL activities that particularly focus on emotional awareness and regulation into my language lessons for adult learners in multicultural classrooms. My goal is to create a balanced learning environment that nurtures both academic growth and emotional intelligence. My presentation will summarize my ongoing SEL research in two continents. I will also display how an indigenous understanding of mindfulness, specifically Māori mindfulness, has been informing my research. Additionally, I will share insights and feedback from student surveys and interviews conducted at the conclusion of my new cycle of action research, which involves over 20 adult students in a B2 Academic English class. Through these findings, I aim to highlight the positive impact of SEL, as it supports not only language proficiency but also the interpersonal skills needed for success in academic and workplace settings.